STRATEGI PENGUATAN BRANDING PRODUK KOPI KUDA BERKAIT MELALUI INOVASI KEMASAN DAN EDUKASI DIGITAL MARKETING BAGI UMKM DESA SEBONG PEREH - Imran Ilyas; Satrio Bimo Saputro; Indra Bastian Tahir; Muhammad Isa Alamsyahbana; David Dwi Malya Putra; Muhammad Nursyahdani; Novi Komalasari; Nurul, Nurul; Rezky Pranatha; Selvi Wahyuningsih; Silvia Yohani; Viena, Viena (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aimed to improve the competitiveness of the UMKM Kopi Kuda Berkait in Sebong Pereh Village through packaging innovation and digital marketing education for local UMKM. The innovation involved designing modern, hygienic, and functional packaging to enhance the product's appeal and strengthen its brand identity. Digital marketing education was provided to the UMKMs in Sebong Pereh Village, including the use of e-commerce platforms such as Shopee. The implementation methods included interviews, observations, documentation, participation, and socialization. As a result, the packaging innovation successfully enhanced the branding of Kopi Kuda Berkait, while the digital marketing education helped local UMKMs understand digital marketing strategies to expand their market reach